Evaluation of Human Thermal Comfort and Microbial Analysis in an Evaporative Cooling Room - Sudprasert, Sudaporn; Maruyama, Sasicha (Journal of Architectural/Planning Research and Studies (JARS), 2022)
In Thailand, evaporative air coolers (EAC) are common in outdoor and semi-outdoor areas. Exploring the possibility of using an EAC in an indoor area, this research aims to determine its benefits in a natural, ventilated room during summer and winter. In terms of human thermal comfort, these benefits are evaluated through the CBE Thermal Comfort Tool with environmental parameters collected from the testing room. Bacterial growth due to increased humidity is analyzed based on bacterial counts in the opened Petri dishes. The results from the testing room with EAC show that air temperature reduces by 1.4 - 4.4 °C during winter and 3.3 - 3.5 °C during summer with a relative humidity increase of 2.3 - 13.1%. Thermal comfort was found to depend on indoor air temperature and air velocity. During winter, it was slightly improved by the use of an EAC, with an elevated percentage of people dissatisfied (PPD) due to low air temperature and high air velocity. The evaporative, cooled air also enhances thermal comfort in summer with less PPD. Increasing air velocity to provide thermal comfort is more suitable in summer than in winter. More bacteriological colonies formed in the room with an EAC than in the room with natural air by 33-55 units. The air quality in the EAC room according to IMA standards was Fair-Good, dropped from Good-Very Good in the natural-air room. This study confirms that the EAC improved thermal comfort in the natural ventilation room during both summer and winter. However, the room air was impure with the increase in microbial activity due to high air temperature and humidity.